FINKNIGHT: An Educational Game for Character Building in Financial Literacy, Tax Compliance, and Charitable Acts - Luhsasi, Dwi Iga; Permatasari, Carolina Lita; Triwantoro, Agus (Proceedings International Conference on Education Innovation and Social Science, 2024)
Financial literacy, which is the basis for a person's financial behavior, is very important to instill in everyone. The reality shows that people already understand financial literacy, but only a few understand and apply it. Therefore, the development of educational games is necessary to help people to understand them in depth and apply them. FINKNIGHT is an innovative educational game designed to instill financial literacy skills and cultivate character traits related to financial management, tax compliance, and philanthropy. Through immersive gameplay, players are immersed in a virtual board where they must navigate financial challenges, fulfill tax obligations, and engage in charitable acts. By making decisions within the game environment, players learn the fundamentals of budgeting, saving, investing, and tax planning, while also understanding the ethical and social dimensions of financial behavior. FINKNIGHT integrates interactive scenarios, quizzes, and simulations to provide hands-on learning experiences that promote critical thinking and responsible decision-making. By gamifying financial education, FINKNIGHT aims to empower players with the knowledge, skills, and values necessary to achieve financial well-being and contribute positively to society. On the result, a tool called FINKNIGHT is a good tool which means that it can help people, especially students, in the learning financial literacy.